Metapopulation dynamics of multiple species in a heterogeneous landscape. Issue 3 (8th April 2022) - Pantel, Jelena H.; Lamy, Thomas; Dubart, Maxime; Pointier, Jean‐Pierre; Jarne, Philippe; David, Patrice
Abstract: Characterizing the diversity of demographic strategies among species can inform research in topics such as trait syndromes, community stability, coexistence, and ecological succession. However, this diversity can depend on the spatial scale considered: at the landscape scale, species often form metapopulations, that is sets of local, sometimes short‐lived, populations, inhabiting discrete habitat patches. Metapopulation dynamics are most frequently analyzed in individual species or pairs of interacting species because of the large amount of data required for multiple species, and because species vary in their perceptions of what constitutes a favorable or unfavorable habitat. Here we evaluate, using a case study, whether a metapopulation model can be used to generate accurate estimates of demographic parameters and to describe the diversity of dynamics, responses to environment, and prospects of long‐term persistence in a guild of species inhabiting a common fragmented landscape. We applied this approach to a guild of 22 mollusk species that inhabit freshwater habitats on two islands of Guadeloupe, to compare metapopulation dynamics among species. We analyzed a 15‐year time series of occupancy records for 278 sites using a multistate occupancy model that estimated colonization and extinction rates as a function of site‐specific and year‐specific environmental covariates, then used model results to simulate future island metapopulation dynamics. Despite the diverse array of metapopulation trajectories—a mix of species with either stable, increasing, declining, or fluctuating metapopulations—and the inherent challenges associated with such data (e.g., imperfect detection, spatial and temporal heterogeneity), our model accurately captured among‐patch variation in suitability for many mollusk taxa. The dynamics of rare species or species with habitat preferences not fully captured by the retained set of covariates were less well described. For several species, we detected a negative correlation between extinction and colonization. This variation in habitat suitability created species‐specific extinction‐resistant pockets in the landscape. Our comparative analysis also revealed that species had distinct strategies for metapopulation dynamics, such as "fast‐turnover" species with both a high proportion of occupied sites and a high rate of site extinction in the landscape.